2017
DOI: 10.18517/ijaseit.7.5.1592
|View full text |Cite
|
Sign up to set email alerts
|

Population and Diversity of Indigenous Arbuscular Mycorrhizal Fungi from Shallots Rhizosphere in Different Altitudes in West Sumatra

Abstract: Arbuscular Mycorrhizal Fungi (AMF) of indigenous believed to be more efficient and effective in helping the growth of plants. Observations diversity of indigenous AMF conducted at several locations of centers of shallot cultivation in West Sumatra. AMF existence is closely related to environmental factors (abiotic and biotic). Sampling was based on the different in altitude : highland (Alahan Panjang), middle land (Saniang Baka) and lowland (Kambang). Indigenous AMF identification using morphological approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Glomus sp1, Glomus sp2, Glomus sp3, a mixed those three isolates and control treatment (without applications of AMF). Source of isolates from the results of research by Susila et al (2017). Data analyzed used the Statistical Tool for Agricultural Research (STAR) program.…”
Section: Methodsmentioning
confidence: 99%
“…Glomus sp1, Glomus sp2, Glomus sp3, a mixed those three isolates and control treatment (without applications of AMF). Source of isolates from the results of research by Susila et al (2017). Data analyzed used the Statistical Tool for Agricultural Research (STAR) program.…”
Section: Methodsmentioning
confidence: 99%
“…Sample had previously been collected from 3(three) locations of centers of shallot cultivation in West Sumatra : AlahanPanjang [4], in the district of Solok (100 0 46'58.7" E-1 0 04'23.5" S), SaniangBaka [4] in the district of Solok (100 0 31'32.2" E-0 0 42'55.7"S) and Kambang [4], in the district of Pesisir Selatan (100 0 42'00.0"-1 0 42'00.0"S). See Figure 2.…”
Section: Origin Of Isolate Amf Indigenous (Exploration Of Amf):-mentioning
confidence: 99%
“…Inoculation of AMF originating from the plant itself (indigenous) is believed to be more able to adapt to the plant. Susilaet al [4], reported 6 isolates of AMF derived from the shallots rhizosphere abundant presence (Isolation Frequncy>40% and Relative Abundant > 3% [5]) See Figure 1. The compatibility between AMF and host plant is one of the factors in getting maximum benefit from AMF activity [6].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Various microorganisms are found in the rhizosphere of plants. Besides Myccorhizal Arbuscular fungi (Susila et al 2017), one of beneficial soil microorganisms for plants is Trichoderma sp. which naturally attacks pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%